The Utilization of Science-Based Digital Teaching Materials as Educational Media for Disaster Mitigation: A Literature Review - Almira Erika Putri; Muhammad Fadhil Khairullah; Rindi Sartika Dwi Oktari; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2026)
This study aims to examine how to use science-based digital teaching materials as an educational tool on how to reduce the impact of disasters through monitoring and literature review. Previous research has typically discussed digital media and disaster education separately, leaving gaps in integrating the two into a unified whole. This study aims to fill this gap by analyzing 6 relevant scientific articles, using a qualitative literature review approach that includes content analysis and systematic thematic development.The results indicate that  the use of science-based digital teaching materials successfully improves conceptual understanding, scientific literacy skills, and disaster preparedness. Three key findings were found: media such as simulations and videos facilitate better conceptual understanding because they use images; incorporating examples from the surrounding environment enhances students' awareness and enables them to make better decisions; and the use of digital platforms makes learning more engaging and flexible. However, implementation still faces obstacles due to limited access to technology, teachers' inadequate digital skills, and the limited availability of materials based on local wisdom. Thus, digital teaching materials that apply scientific principles have great potential as effective disaster mitigation educational tools, but require structured and context-appropriate development.